Smart Mom for Disaster Preparedness: Pengasuhan Resilien dalam Meningkatkan Kesadaran Bencana Anak Usia Dini - Sari, Novita; Susanti, Lis; Erlangga, Maulana Deni; Fadilah, Fadilah; Mariam, Mariam; Komariyah, Komariyah; Hulaela, Hulaela; Rosdiana, Rosdiana; Nurjanah, Nurjanah; Sabrina, Annisa; Hikmatullah, Hikmatullah (Universitas Pahlawan Tuanku Tambusai, 2025)
This Community Service Program (PKM) aims to improve the understanding and capacity of parents, especially mothers, in implementing resilient parenting as a strategy to build disaster awareness in early childhood. The activity entitled